Biochar fungal pellet based biological immobilization reactor efficiently removed nitrate and cadmium. (June 2022) - Zheng, Zhijie; Ali, Amjad; Su, Junfeng; Zhang, Shuai; Su, Lindong; Qi, Zening
Abstract: To efficiently and simultaneously remove nitrate (NO3 − -N) and Cd(II) from aqueous solution, a novel type of biochar fungal pellet (BFP) immobilized denitrification bacteria ( Cupriavidus sp. H29) composite was used in a bioreactor. The removal performance of the bioreactor R1 for the initial concentration of 27.7 mg L −1 nitrate and 10.0 mg L −1 Cd(II) reached 98.1 and 93.9% respectively, and the inoculation of strain H29 in bioreactor R1 significantly enhanced the removal efficiency of contaminants. The 3D-EEM spectra analysis showed that the activity of microorganisms in the bioreactor was higher at a lower concentration of Cd(II). FTIR indicated the effect of functional groups in BFP in bioadsorption of Cd(II). In addition, high-throughput analysis of species composition of the microbial community in the bioreactors at different levels demonstrated that strain H29 played a significant part in the bioreactor. This research provided a perspective for simultaneous restoration of nitrate and heavy metals in wastewater, and also enriched the application of fungal pellet (FP) in reactors. Graphical abstract: Image 1 Highlights: Biochar fungal pellet, as composite material, can immobilize denitrifying bacteria. Biochar fungal pellet promoted the denitrification performance of microorganisms. Biological method combined with adsorption enhanced the removal of cadmium. Biological immobilization reactor was efficient to remove nitrate and cadmium. High-throughput showed that strain H29 had great influence in the bioreactor.